The effect of subambient to elevated atmospheric CO₂ concentration on vascular function in Helianthus annuus implications for plant response to climate change - Rico, Christopher (The New phytologist, 2013)
© 2013 The Authors. New Phytologist © 2013 New Phytologist Trust.